2021
DOI: 10.1021/acs.jmedchem.1c01154
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of IHMT-EZH2-115 as a Potent and Selective Enhancer of Zeste Homolog 2 (EZH2) Inhibitor for the Treatment of B-Cell Lymphomas

Abstract: The enhancer of zeste homologue 2 (EZH2) is the catalytic subunit of polycomb repressive complex 2 that catalyzes methylation of histone H3 lysine 27 (H3K27). Overexpression or mutation of EZH2 has been identified in hematologic malignancies and solid tumors. Based on the structure of EPZ6438 (1) and the binding model with PRC2, we designed a series of analogues aiming to improve the activities of EZH2 mutants. Structure–activity relationship (SAR) exploration at both enzymatic and cellular levels led to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Inhibition of the hERG channel was assayed using a stable transfected human embryonic kidney cell line (HEK293) by a whole-cell patch clamp at room temperature (22–24 °C) as described . The effects of CHNQD-01255 and quinidine (30 μM, positive control) were normalized to the corresponding control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of the hERG channel was assayed using a stable transfected human embryonic kidney cell line (HEK293) by a whole-cell patch clamp at room temperature (22–24 °C) as described . The effects of CHNQD-01255 and quinidine (30 μM, positive control) were normalized to the corresponding control.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibition of the hERG channel was assayed using a stable transfected human embryonic kidney cell line (HEK293) by a whole-cell patch clamp at room temperature (22−24 °C) as described. 42 The effects of CHNQD-01255 and quinidine (30 μM, positive control) were normalized to the corresponding control. Whole-cell recordings were collected with the patch clamp amplifier HEKA EPC10 and PATCHMASTER V2X60 (HEKA Instruments, Inc., D-67466 Lambrecht, Pfalz, Germany).…”
Section: ■ Associated Contentmentioning
confidence: 99%
“…Zhou et al of Hefei Institutes of Physical Sciences designed a series of analogues to improve the activity of EZH2 mutants based on the structure of tazemetostat . A carbonyl amide group was installed in the central part, and it was found that cyclopropyl-substituted 10 ( F = 15.1%) had a better inhibitory effect on EZH2 and had antiproliferative activity on WSU-DLCL2 cells (IC 50 = 200 nM).…”
Section: Tazemetostat and Ezh2 Inhibitors In Clinical Trialsmentioning
confidence: 99%
“…33 Zhou et al of Hefei Institutes of Physical Sciences designed a series of analogues to improve the activity of EZH2 mutants based on the structure of tazemetostat. 36 A carbonyl amide group was installed in the central part, and it was found that cyclopropyl-substituted 10 (F = 15.1%) had a better inhibitory effect on EZH2 and had antiproliferative activity on WSU-DLCL2 cells (IC 50 = 200 nM). They continued to modify the tail structure and found that the morpholinyl group in 10 was replaced by the piperazinyl group substituted by cyclopropylmethyl, which converted phenyl to pyridine (11, EZH2(Y641F) IC 50 = 24.4 nM, F = 9.4%) and enhanced the inhibition of EZH2(Y641F).…”
Section: Tazemetostat and Ezh2 Inhibitors Inmentioning
confidence: 99%
“…The enhancer of zeste homologue 2 (EZH2) is the catalytic subunit of polycomb repressive complex 2 (PRC2), which catalyzes the transfer of one to three methyl groups from the cofactor S-adenosylmethionine (SAM) to the ε-NH 2 group of H3 lysine 27 (H3K27), resulting in three different methylation states of H3K27 (mono-, di-, or trimethylation of H3K27). , Among others, trimethylation of H3K27 (H3K27me3) contributes to the modification of the chromatin structure, resulting in the repression of gene transcription that promotes differentiation and restrains proliferation in normal cells . Overexpression of EZH2 has been observed in multiple solid and malignant tumors, including tumors of prostate, breast, kidneys, and lungs, myeloma, and leukemia, and its expression level often correlates with disease progression and poor prognosis. Additionally, activating point mutations in the catalytic SET domain of EZH2, such as Y641N, Y641F, and A677G, have been identified in diffuse large B-cell lymphoma (DLBCL) and follicular lymphoma (FL). , Collectively, EZH2 has attracted increasing attention as an attractive anticancer target in the past decade. …”
Section: Introductionmentioning
confidence: 99%